Cloaking by coating: how effectively does a thin, stiff coating hide a soft substrate?. Issue 19 (14th April 2020) - Box, Finn; Jacquemot, Cyprien; Adda-Bedia, Mokhtar; Vella, Dominic
Abstract : From human tissue to fruits, many soft materials are coated with a thin layer of a stiffer material. We study the effect of such a coating on the stiffness of the combined object to touch, and show that the size of the probe affects the measured result. Abstract : From human tissue to fruits, many soft materials are coated by a thin layer of a stiffer material. While the primary role of such a coating is often to protect the softer material, the thin, stiff coating also has an important effect on the mechanical behaviour of the composite material, making it appear significantly stiffer than the underlying material. We study this cloaking effect of a coating for the particular case of indentation tests, which measure the 'firmness' of the composite solid: we use a combination of theory and experiment to characterize the firmness quantitatively. We find that the indenter size plays a key role in determining the effectiveness of cloaking: small indenters feel a mixture of the material properties of the coating and of the substrate, while large indenters sense largely the unadulterated substrate.